Snowball Throwing: The Critical Thinking and Self-Efficacy Revolution - Jumari, Eko Okta (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
The ability to think critically and self-efficacy are essential skills for students in the modern era. However, effective learning methods to improve these two skills remain underexplored. This research evaluates the effectiveness of the snowball-throwing method in improving the critical thinking skills and self-efficacy of vocational school students. This research involved class X students in one of the Bandung City Vocational Schools as samples. The method in this research uses the Embedded mixed method which is collected through test questions, observations, questionnaires, and interviews. The research results showed that Snowball Throwing significantly improved critical thinking skills, as seen from increased student analysis, evaluation, and synthesis. Apart from that, students' self-efficacy also increases, marked by increased self-confidence in completing assignments and facing challenges. This conclusion indicates that Snowball Throwing is an effective learning method for improving critical thinking skills and self-efficacy in vocational schools.